Public awareness of testicular cancer and self-examination in Turkey: A multicenter study of Turkish Urooncology Society - (:unkn) unknown (My University, 2013)
Background: Testicular self-examination is the easiest and cheapest way to scan testicular cancer. However, the public awareness about testicular self-examination is very low. We aimed to investigate the public awareness of Turkish people about testicular cancer and testicular self-examination. Methods: We performed a survey consisting of 10 questions concerning testicular cancer and testicular self-examination in 799 students in the first year of 12 different medical schools. Aiming for a common method of data collection, the questionnaires were administered to the students during a class just before the lesson started. The whole data from all of the centers were pooled in a common data-base file. Results: Eighty-nine (11.1%) of the participants reported that they had knowledge about testicular cancer, but only 11 (1.4%) of them answered all the questions about testicular cancer correctly. Eight (1%) of the participants reported that they had been performing testicular self-examination routinely once a month. Four (0.5%) of them were both well informed about testicular cancer and had been performing testicular self-examination once a month as suggested. Conclusion: The present study showed that awareness on testicular cancer and testicular self-examination is very low and suggests a need for efforts in Turkey to increase public awareness and education. © 2013 Elsevier Inc.
Keywords: Survey; Testicular cancer; Testicular self-examination